Pengaruh Terapi Peregangan Otot Pernafasan terhadap Peningkatan Kapasitas Vital Paru Pasien Asma di Rumah Sakit Grandmed Lubuk Pakam - Syatria wati; Juni Mariati Simarmata; Arfah May Syara; Desika Wali Pardede (STIKes Santa Elisabeth Medan, 2021)
Background: Asthma is a disease of shortness of breath due to narrowing of flight routes. A decrease in the expiratory rate and inspiratory volume will decrease the lung fundamentals. Asthmatic patients need exercise to expand the lung boundaries which is much needed. Respiratory muscle stretching exercises are activities to maintain and build the adaptability or adaptability of the respiratory muscles.Methods: The aim of this study was to determine the impact of extended treatment on respiratory muscles to establish lung boundaries that are important for asthmatic patients. This examination technique is a quantitative report using a semi-test design with a one gathering pretest posttest configuration approach. The test consists of 17 respondents, this instrument uses spirometry and observation sheets. The results of the bivariate test used a p value of = .000 < (0.05).Result: This test shows that there is an effect of respiratory muscle stretching therapy on increasing vital lung capacity of asthmatic patients.Conclusion: For the Bivariate analysis, the results obtained based on the paired sample T-test there were significant differences between before and after with the results of the P Value index = .000 < (0.05). The conclusion is that Ho is rejected. So that there is an effect of respiratory muscle stretching therapy on increasing vital lung capacity of asthma patients at GrandMed Hospital in 2020.